Influence of day of surgery on mortality following elective colorectal resections. Issue 10 (24th June 2015) - Vohra, R S; Pinkney, T; Evison, F; Begaj, I; Ray, D; Alderson, D; Morton, D G
Abstract: Background: The aim of this study was to investigate whether the increased mortality previously identified for surgery performed on Fridays was apparent following major elective colorectal resections and how this might be affected by case mix. Methods: Patients undergoing elective colorectal resections in England from 2001 to 2011 were identified using Hospital Episode Statistics. Propensity scores were used to match patients having operations on a Friday in a 1 : 1 ratio with those undergoing surgery on other weekdays. Multivariable analyses were used to investigate overall deaths within 1 year of operation. Results: A total of 204 669 records were extracted for patients undergoing major elective colorectal resections. Patients who had surgery on Fridays were more deprived (4780 (17·1 per cent) of 27 920 versus 28 317 (16·0 per cent) of 176 749; P < 0·001), a greater proportion had had an emergency admission in the 3 previous months (7870 (28·2 per cent) of 27 920 versus 48 623 (27·5 per cent) of 176 749; P = 0·019), underwent minimal access surgery (4565 (16·4 per cent) of 27 920 versus 23 783 (13·5 per cent) of 176 749; P < 0·001) and had surgery for benign diagnoses (6502 (23·3 per cent) of 27 920 versus 38 725 (21·9 per cent) of 176 749; P < 0·001) than those who had surgery on Mondays to Thursdays. In a matched analysis the odds ratio for 30-day mortality after colorectal resections performed on Fridays compared with other weekdays was 1·25 (95 per cent c.i. 1·13 to 1·37); odds ratios for 90-day and 1-year mortality were 1·16 (1·07 to 1·25) and 1·10 (1·04 to 1·16) respectively. Conclusion: Patients selected for colorectal resections on Fridays had a higher mortality rate than patients operated on from Monday to Thursday and had different characteristics, suggesting that increased mortality may reflect patient factors rather than hospital variables alone. Abstract : Friday is different